The digital workflow in dentistry: adoption and challenges - Chu, Seng Boon; Ooi, Huay Shuan (IIUM Journal of Orofacial and Health Sciences, 2025)
The incorporation of digital technologies has brought about a revolution in the profession of dentistry, resulting in greater diagnostic accuracy, enhanced patient outcomes and streamlined operations. Intraoral scanners, cone beam computed tomography (CBCT), computer-aided design/computer-aided manufacturing (CAD/CAM) systems, and 3D printing have profoundly influenced the field of prosthodontics, implantology and orthodontics. These developments provide enhanced precision in planning, manufacture and customization of dental prostheses and surgical guides. Nonetheless, the implementation of digital workflows entails problems such as elevated expenses, steep learning curves and the need for ongoing equipment maintenance. This study examines the advantages and obstacles of digital dentistry, emphasizes technological improvements, and considers future directions, including the potential for AI integration. A balanced approach, addressing the technological and clinical challenges, is crucial for maximizing the benefits of digital tools in modern dental practice.